2018
DOI: 10.1002/sdtp.12222
|View full text |Cite
|
Sign up to set email alerts
|

75‐2: Novel Plane Source FMM Evaporation Techniques for Manufacturing of 2250ppi flexible AMOLEDs

Abstract: The linear source FMM evaporation can only provide 600ppi AMOLED devices because of the shadow effect so that new concept of FMM patterning technology is needed in order to fabricate the 2250ppi AMOLEDs. Recently, the plane source FMM evaporation techniques has been developed to show a dramatically suppressed shadow effect and to measure the 0.18um of shadow distance and Hwang's mixing for the new way of EML layer process. The green color OLED device has been fabricated by the plane source evaporation to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The plane source evaporator can control the angle of incidence of the organic molecule evaporated from the metal plate for the high ppi micro-OLED. [3] The plane source FMM evaporator consists of FMM, metal plate, point source in the high vacuum chabmer. When the TFT substrate goes into the evaporator, the TFT substrate is aligned with the FMM and the point source evaporates the organic molecules to deposit the donor film on the metal plate.…”
Section: Plane Source Evaporatormentioning
confidence: 99%
“…The plane source evaporator can control the angle of incidence of the organic molecule evaporated from the metal plate for the high ppi micro-OLED. [3] The plane source FMM evaporator consists of FMM, metal plate, point source in the high vacuum chabmer. When the TFT substrate goes into the evaporator, the TFT substrate is aligned with the FMM and the point source evaporates the organic molecules to deposit the donor film on the metal plate.…”
Section: Plane Source Evaporatormentioning
confidence: 99%
“…By the vertical vapor deposition, the smaller angle of incidence of the molecules makes the less shadow distance behind the FMM. [2,3,15]…”
Section: Plane Source Evaporationmentioning
confidence: 99%
“…Furthermore, recent studies have showed that CSS, due to its conformal deposition characteristics, can significantly lower the shadowing effect associated with VTE when used with FMM. [1][2][3] A critical issue of the CSS is the deposition of the emitter layer (EML), which typically has a host-dopant composition. To ensure a uniform concentration of dopant molecules in the host matrix throughout the thickness of the film, the dopant and host molecules must co-evaporate at a fixed rate ratio as they are transferred from the donor substrate to the receiver substrate.…”
Section: Introductionmentioning
confidence: 99%